The Relationship Between the Socio-Cultural Environment and Family Support With the Participation of the Husband as an Acceptor of Family Planning in Tinelo Village, Tilango District - Angraini Nani; Herlina Jusuf; Dewi Suryaningsi Hiola (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The participation of husbands in family planning programs in Indonesia is still relatively low, which is influenced by several factors, including the socio-cultural environment and family support. It is not easy for the public to accept that men actively participate in family planning programs for various reasons. Cultural barriers are still dominant to male contraception. The purpose of the study was to determine the relationship between the socio-cultural environment and family support with the participation of the husband as a family planning acceptor in Tinelo Village. Types of analytical survey research with a cross-sectional approach. Sampling was done using purposive sampling techniques. The research population of all couples of childbearing age in Tinelo Village, Tilango District amounted to 359 with a sample of 189 respondents. The data was analyzed with the chi-square test. The results of the study showed that there was a relationship between the socio-cultural environment and the participation of the husband as a family planning acceptor (p-value = 0.00 < ? = 0.05) and there was a relationship between family support and the participation of the husband as a family planning acceptor (p-value = 0.00 < ? = 0.05). In conclusion, the variables of socio-cultural environment and family support are related to the variables of the husband's participation in becoming a family planning acceptor in Tinelo Village, Tilango District. It is hoped that this research will be an input to the Health Center and the Family Planning Extension Center in an effort to improve health services, especially in family planning services for husbands.